Pendapatan Usaha Peternakan Ayam Broiler di PT. Unggas Jaya Kecamatan Selebar Kota Bengkulu - Rita Feni; Budi Pangestu (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Feni R, Pangestu B. 2021. revenue of Broiler Chicken in PT. Unggas Jaya Selebar district Bengkulu City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 545-554. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). This study aimed to analyze revenue from broiler chicken farm, PT Unggas Jaya. The study was done in broiler chicken farm PT Unggas Jaya at Selebar district, Bengkulu city. Method used in the study was case study. This study used primary and secondary data. Primary data was taken directly from study subject. Secondary data obtained from revant agencies. Interview method used to obtain primary data by using questionnaire to the venture’s owner such as administration and organization data, fixed cost, variable cost, production and marketing data. Meanwhile secondary data obtained from district office and agriculture and husbandry office. Data analysis using Operating profit, Net profit, R/C ratio, Profile rate and Profitability. The study result shows that broiler chicken farm PT Unggas Jaya is profitable and deserve to be developed with analysis result as follows Operating profit Rp 839.008.000, Net profit Rp 429.081.00, RC ratio 1.105, Profit Rate 10.58%, and Profitability 5.56%.